Purification and characterisation of endogenous unanchored polyubiquitin - Gopala Krishna, Varun (2017)
The 76 amino-acid protein ubiquitin is peculiar in its ability to covalently modify substrate proteins. The complexity and diversity in structure and function, of this posttranslational modification is increasingly evident and has been extensively scrutinized. However, the existing notion for ubiquitin to be functionally relevant when covalently linked to substrates was recently found to be dispensable. Pioneering work by Chen’s group has shown that unanchored (non-substrate bound) polyubiquitin chains are just as effective in regulating various cellular processes and presented compelling evidence about the influence of unanchored polyubiquitin chains in regulating cell signalling. That said, not enough emphasis has been placed in developing tools for the direct isolation and characterisation of endogenous unanchored polyubiquitin chains.